2020
DOI: 10.2174/1745017902016010165
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and Burnout are Related to Lifetime Mood Spectrum in Emergency Healthcare Operator

Abstract: Background: PTSD and burnout are frequent conditions among emergency healthcare personnel because exposed to repeated traumatic working experiences. Increasing evidence suggests high comorbidity between PTSD and mood symptoms, particularly depression, although the real nature of this relationship still remains unclear. The purpose of this study was to investigate the relationship between PTSD, burnout and lifetime mood spectrum, assessed by a specific scale, among health-care professionals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 65 publications
0
14
0
3
Order By: Relevance
“…This can be accomplished by implementing strategic health-workforce plans, support and capacity-building, and by providing suitable surveillance measures. These may enable the detection of impaired communication and critical events in order to lighten their impact on HCWs’ mental health, allowing regular screening for depression and PTSD for HCWs ( Carmassi et al, 2020 ; Kisely et al, 2020 ). On the other hand, feeling safe with the available personal equipment seems to play a protective role against depressive symptoms as well.…”
Section: Discussionmentioning
confidence: 99%
“…This can be accomplished by implementing strategic health-workforce plans, support and capacity-building, and by providing suitable surveillance measures. These may enable the detection of impaired communication and critical events in order to lighten their impact on HCWs’ mental health, allowing regular screening for depression and PTSD for HCWs ( Carmassi et al, 2020 ; Kisely et al, 2020 ). On the other hand, feeling safe with the available personal equipment seems to play a protective role against depressive symptoms as well.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of longitudinal research investigating the role of burnout on mental health. One study among nurses found an association between lifetime depressive symptoms and burnout (Carmassi et al, 2020); however, the direction of the relationship between mental health and burnout remains unclear. Understanding the relationship between burnout and mental disorders is important for early detection of mental distress and to provide early intervention to promote mental well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found strong links between burnout and depression (35,36). In a study by Duan-Porter et al (37) there was a positive relationship between mental disorder symptoms and burnout among nurses, and burnout was significantly associated with higher levels of anxiety, stress, and depression.…”
Section: Discussionmentioning
confidence: 92%